News Content Production Strategy at Metro Tv: A Case Study of The Mtvn Lens Digital Program - Calista Vanis; Arifin Saleh Harahap; Salman Salman; Ballian Siregar (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study examines the news content production strategy developed by Metro TV through its digital initiative, MTVN Lens, in response to media convergence and shifts in audience consumption patterns. The expansion of digital platforms has compelled television news organizations to rethink newsroom routines and adapt news formats to remain competitive, particularly in engaging younger audiences who increasingly rely on online media. This research is grounded in a constructivist paradigm and employs a descriptive qualitative approach with a case study strategy. Primary data were collected through semi-structured in-depth interviews with members of the MTVN Lens production team, supported by direct observation of newsroom activities and documentation of content production processes at Metro TV. Data analysis was conducted using thematic analysis, with validity ensured through source and technique triangulation. The analysis is guided by Media Convergence Theory proposed by Henry Jenkins, emphasizing the integration of traditional and digital media practices. The findings reveal that MTVN Lens adopts a hybrid production model that combines core television journalism values with digital media attributes. This model is reflected in adaptive editorial planning aligned with digital trends, flexible production workflows, and the distribution of news content across multiple digital platforms. Through this strategy, Metro TV is able to maintain journalistic credibility while strengthening its engagement with digital audiences.